2005
DOI: 10.1099/vir.0.80794-0
|View full text |Cite
|
Sign up to set email alerts
|

Rolling-circle amplification of Torque teno virus (TTV) complete genomes from human and swine sera and identification of a novel swine TTV genogroup

Abstract: Multiply primed rolling-circle amplification is a novel technology that uses bacteriophage phi29 DNA polymerase to amplify circular DNA molecules, without the need for prior knowledge of their sequences. In an attempt to detect Torque teno virus (TTV), rolling-circle amplification was used to amplify DNA extracted from eight human and four pig serum samples. All samples gave high molecular weight (>30 kb) amplification products. By restriction endonuclease digestion, these products generated DNA fragments whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
106
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 27 publications
3
106
1
2
Order By: Relevance
“…TTSuVs have similar genomic organization with human-infecting TTVs but share less than 45 % nt sequence identity (Niel et al, 2005;Okamoto et al, 2002). Recent studies also demonstrated a high degree of genetic variability between TTSuV1 and TTSuV2 (Cortey et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…TTSuVs have similar genomic organization with human-infecting TTVs but share less than 45 % nt sequence identity (Niel et al, 2005;Okamoto et al, 2002). Recent studies also demonstrated a high degree of genetic variability between TTSuV1 and TTSuV2 (Cortey et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Sd-TTV2p by itself composes novel TTV genogroup 2. 15 A number of researchers have reported TTV prevalence in various situations. 6,8 Coinfection with different genogroups of TTV in an individual was found to be common.…”
mentioning
confidence: 99%
“…After the first finding of swine TTV in 2004, different genogroups in pigs were subsequently identified. 13,15 Porcine TTV isolates Sd-TTV31 and Sd-TTV1p have a relatively high nucleotide sequence identity (69.6%) and are classified as TTV genogroup 1. Sd-TTV31, a prototype of genogroup 1, and Sd-TTV2p, a recently sequenced swine TTV, share a low nucleotide sequence identity (44%) with Sd-TTV31.…”
mentioning
confidence: 99%
“…The ORF2 coding sequences were amplified from plasmids containing TTV genomic DNA. The study included five strains of different species from four genogroups: Gr1 TTV3 HEL32, Gr2 TTV6 LTT6, Gr3a TTV13 3h, Gr3b TTV15 5A and Gr4 TTV29 ViPi08 (Diniz-Mendes et al, 2004;Kakkola et al, 2002;Niel et al, 2005). The details of each strain are depicted in Table S2; the primers used to amplify the ORF2 fragments are shown in Table S3.…”
Section: Methodsmentioning
confidence: 99%